Customer service at Companies Commission of Malaysia (Suruhanjaya Syarikat Malaysia or SSM), Melaka / Mohd Zaki Shazwani Idris - Idris, Mohd Zaki Shazwani (Faculty of Business and Management, 2010)
Companies Commission of Malaysia (Suruhanjaya Syarikat Malaysia or SSM), Melaka is a statutory body which regulates companies and businesses. Furthermore, Companies Commission of Malaysia (Suruhanjaya Syarikat Malaysia or SSM) also responsible to control the regulation acts under their power field. Therefore, Companies Commission of Malaysia (Suruhanjaya Syarikat Malaysia or SSM) has the power to sue the businesses and companies that not follow the registration rules. As a one stop centre, Companies Commission of Malaysia (Suruhanjaya Syarikat Malaysia or SSM), Melaka dealing with their entire customer within Peninsular Malaysia. It is important to ensure the entire customer feel confident and comfortable when dealing with the organization. Due to the complaint from the customer the researcher does the research study on the problem encountered by customers at Companies Commission of Malaysia (Suruhanjaya Syarikat Malaysia or SSM), Melaka that comes with objective to measure the issue that leads to the problem. Next, to generate the possible recommendation and finding that helps to solve the problem. The study develops to see the problem that customer faces at Companies Commission of Malaysia (Suruhanjaya Syarikat Malaysia or SSM), Melaka. This study will discuss about the there are too many flows that customer have to wait before they gain their license of registration of business. Furthermore, there are some facilities needed by the customer but not available near the organization. This study also will discuss specialty for ‘OKU’. This is important for those who are disabling to be given priority when dealing within the organization.